1999
DOI: 10.1073/pnas.96.11.6025
|View full text |Cite
|
Sign up to set email alerts
|

Making artificial antibodies: A format for phage display of combinatorial heterodimeric arrays

Abstract: The gene VII protein (pVII) and gene IX protein (pIX) are associated closely on the surface of filamentous bacteriophage that is opposite of the end harboring the widely exploited pIII protein. We developed a phagemid format wherein antibody heavy-and light-chain variable regions were fused to the amino termini of pVII and pIX, respectively. Significantly, the fusion proteins interacted to form a functional Fv-binding domain on the phage surface. Our approach will be applicable to the display of generic peptid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
93
1
1

Year Published

2000
2000
2010
2010

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 151 publications
(96 citation statements)
references
References 34 publications
(41 reference statements)
1
93
1
1
Order By: Relevance
“…However, a similar body of data concerning the proteins pVII and pIX remains to be acquired. Recently, we elucidated the orientation of pVII and pIX on the phage surface and, for the first time, showed that pVII and pIX could be used to individually display fusion proteins, notably the V H and V L of the antibody Fv fragment (33). Encouraged by these results, we explored the further application of pIX to display a library of human scFvs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a similar body of data concerning the proteins pVII and pIX remains to be acquired. Recently, we elucidated the orientation of pVII and pIX on the phage surface and, for the first time, showed that pVII and pIX could be used to individually display fusion proteins, notably the V H and V L of the antibody Fv fragment (33). Encouraged by these results, we explored the further application of pIX to display a library of human scFvs.…”
Section: Discussionmentioning
confidence: 99%
“…Significantly, large, nonimmune or ''naïve'' antibody-phage libraries displayed on pIII have proven to be a general method to readily isolate high-affinity and specific human antibodies against a variety of target antigens (28)(29)(30)(31)(32). We previously showed that pVII and pIX could be used to display the antibody variable heavy-chain region (V H ) and variable light-chain region (V L ), respectively, and that this heterodimeric presentation afforded a viable Fv with fully functional binding and catalytic activities (33). In the present study, we used a pIX display alone for the efficient construction of a large, naïve human antibody library based on the fusion of the scFv format to the N terminus of pIX.…”
mentioning
confidence: 99%
“…All the other coat proteins of the filamentous bacteriophage can and have been utilized for phage display. The pVII and pIX minor coat proteins have been used together for two-chain antibody display (Gao et al, 1999) and pVI display for peptide and cDNA display. In contrast to the pIII and pVIII display systems, the C-terminus of the pVI protein projects outwards and allows display of peptides and proteins with a free C-terminus (Hufton et al, 1999).…”
Section: Phage Display Formatsmentioning
confidence: 99%
“…A single report has detailed the display of proteins fused to the carboxy-terminus of the gene-6 minor coat protein, but display levels were about 100-fold lower than those observed with aminoterminal P3 display [5]. Another report has indicated that the two remaining coat proteins (the gene-7 and gene-9 minor coat proteins) both support amino-terminal fusions but not carboxy-terminal fusions [6]. Crameri et al [7] have also developed a heterodimeric display system in which one member of a heterodimer pair is displayed as a fusion to the aminoterminus of P3, and the second member is co-expressed with a carboxy-terminal fusion.…”
Section: Introductionmentioning
confidence: 99%
“…could be useful in studies of heterodimeric protein^protein interactions [6] and enzyme^substrate interactions [21].…”
Section: Uses For Carboxy-terminal Phage Displaymentioning
confidence: 99%